HIV Treatment-as-Prevention Research at a Crossroads - Bärnighausen, Till (Public Library of Science, 2014)
In light of changing WHO guidelines for HIV treatment, Till Bärnighausen and colleagues consider how large-scale HIV treatment-as-prevention trials can be adapted so that they can remain viable. Please see later in the article for the Editors' Summary